BEAT FREQUENCY AND VELOCITY VARIATION OF IONS IN A MAGNETIZED PLASMA SHEATH FOR DIFFERENT OBLIQUENESS OF THE MAGNETIC FIELD - Adhikari, B. R.; Basnet, S.; Lamichhane, H. P.; Khanal, R. (Journal of Institute of Science and Technology, 2019)
Beat frequency and velocity variation of ions in a magnetized plasma sheath has been numerically investigated by using a kinetic trajectory simulation (KTS) model for varying obliqueness of the external magnetic field in presence of an electric field. Angular dependence of mean value, maximum amplitude, damping constant, frequency of oscillation and beat frequency have been studied. As the obliqueness of the field changes the mean values, beat frequency as well as the maximum amplitude of the velocity components also change but frequency of oscillation remains almost the same.